A Short History of Table-Talk and Live-Action Role-Playing in Japan: Replays and the Horror Genre as Drivers of Popularity. (October 2019) - Kamm, Björn-Ole
Background . The history oflarp, live-action role-play, inJapan may be rather short but documents exponential growth in the entertainment sector as well as in educational gaming. Following trends of related forms ofanalog role-playing games, thehorror genre functions as a motor of increasing popularity. Aim . This article explores the development of non-digital role-playing games in the Japanese context in light of the online video platform niconico popularizing horror role-playing and practical considerations of adopting the genre to live-action play. Method .Cyberethnographic fieldwork including participant observation at larps between 2015 and 2018 forms the data basis for this article, followed by qualitative interviews with larp organizers, larp writers, and designers of analog games as well as observations online in respective webforums. Results .Replays, novelized transcripts of play sessions, have been an entry point into analog role-playing in Japan since the 1980s. With the advent of video sharing sites, replays moved from the book to audio-visual records and a focus on horror games. Creating a fertile ground for this genre, the first indigenous Japanese larp rulebook built on this interest and the ease of access, namely that players do not need elaborate costumes or equipment to participate in modern horror. Discussion . The dominant form of larps in Japan are one-room games, that work well with horror mysteries and function as a low threshold of accessibility. Furthermore, the emotional impact of horror larps, the affective interaction between players and their characters, allows for memorable experiences and so continues to draw in new players and organizers.